Gastroprotective effect of low dose Eugenol in experimental rats against ethanol induced toxicity: Involvement of antiinflammatory and antioxidant mechanism. (10th May 2022) - Hobani, Yahya Hasan; Mohan, Syam; Shaheen, Emad; Abdelhaleem, Aymen; Faruque Ahmad, Md; Bhatia, Saurabh; Abou-Elhamd, Alaa Sayed
Abstract: Ethnopharmacological relevance: Syzygium aromaticum L. volatile oil (clove oil) has been traditionally used for various stomach disorders including inflammatory conditions. Eugenol is the major constituent present in the volatile oil, and it has been established as a gastroprotective agent through many published studies, but the exact and complete mechanism of ulcer protection is not delineated yet. Moreover, it plays precisely the opposite effect in higher dose in antiulcer properties with worsening the ulcer at a higher dose. Aim: This study aims to carry out the prophylactic cytoprotective effect of eugenol with single low doses and explore the probable interrelated underlying transcriptional and translational level mechanism of cytoprotection such as antioxidative, anti-inflammatory, mucous generation in rats using ethanol-induced ulcer model. Methods: Rats were administered with different doses of eugenol before ethanol intragastrically. The effects of the eugenol on mucous production, Nitric oxide generation, PGE2 synthesis, lipid peroxidation were recorded together with cytokines measurement in the blood. TNF-α and IL-6, two key cytokines, were also studied in specific. In addition, studies on the immunohistochemical and gene expression of HSP70 and iNOS indicators have been conducted. Results: According to our findings, Eugenol substantially reduced the ulcer index and completely protected the mucosa from lesions. By restoring the lowered GSH and NP-SH levels, the protective effect of the eugenol was found to be augmented at both doses. This finding has corresponded to an increase in MDA, which was lowered by ethanol administration. Pre-treatment with eugenol on the ethanol-induced ulcer reduced the plasma NO levels and increased PGE2 along with a decreased TNF-α and IL-6 concentration. Additionally, significant transcriptional and translational upregulation of HSP70 and downregulation of iNOS were detected in the eugenol-treated rat stomach tissue. Conclusion: Our findings demonstrated that eugenol had a considerable gastroprotective impact at low doses, which could be attributed to its ability to regulate inflammatory reactions and antioxidant capacity. Graphical abstract: Image 1